Willingness to Pay and Factors that Influence Curcuma xanthorrhiza Use during The COVID-19 in Kiringan Village, Bantul - Hidayati, Listiana; Fatimah, Fitri Andriani (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
The Indonesian government officially announced a positive case of a patient exposed to COVID-19 in 2020. The purpose of the study was to determine the characteristics of the community in Kiringan Hamlet, calculate the willingness to pay (WTP) value for temulawak and determine the factors that influence the WTP value during COVID-19. The method used descriptive-analytical non-experimental, which involved distributing questionnaires to consumers and herbal medicine producers in Kiringan Village, Bantul, Yogyakarta. The number that met the inclusion criteria was 276 respondents. The primary data obtained were then analyzed descriptively, followed by a WTP analysis using the contingent valuation modeling (CVM) approach and a factor analysis using regression analysis. The results showed that the age distribution obtained from 69 respondents was 36-45 years old (25%), the majority of female gender with 156 respondents (57%), education level was high school with 137 respondents (50%), 172 people (62%) with income level below 1,000,000.00 IDR, the average WTP value of temulawak was 10,956.52 IDR. In contrast, the total WTP value of temulawak reached 3,024,000.00 IDR. Occupation factors (p=0.004), number of family members (p=0.040), and duration of consumption (p=0.005) also affected the WTP of temulawak.